Answer:
18/23=18/23
Step-by-step explanation:
This problem is already in simplest form.
Hope this helped!!!!
We have that
the expression 2f + 4f + 2 – 3-------> we can group it (2f+4f)+(2-3)
(2f+4f)+(2-3)=(6f-1)
therefore
the expression [2f + 4f + 2 – 3] is equivalent to [6f-1]
if the expression [6f-1] for f=3 is 17
then
the expression [2f + 4f + 2 – 3] for f=3 is also 17
<span>let's check it
</span>[2*3 + 4*3 + 2 – 3]--------> [6+12+2-3]=[20-3]=17------> is ok
<span>This is a quadratic equation . We order to equate to zero
</span>2x²<span> – 7 = 9
</span>
2x² - 7-9 = 0
2x² - 16 = 0
This equation is a binomial
2* (x² - 8) = 0
<span>We choose the simplest method . The equation with practice it can be calculated in the memory
</span><span>
The product is equal to 0 if one of the factors is zero
</span>
2≠0 ∨ x² - 8 = 0
x² = √8
x = √8 ∨ x= - √8
Answer : x = √8 ∨ x = -√8
Multiply top equation by -2, then add equations so b drops out....solve for a...plug in a to get b